The Value of Aesthetic Value: Aesthetics, Ethics, and The Network Theory. - Matravers, Derek (Disputatio: International Journal of Philosophy, 2021)
The standard discussion of the relation between aesthetics and ethics tends to avoid the fundamental question: how are those two values ranked against each other in terms of importance. This paper looks at two arguments, the 'resource allocation argument' and the 'relative weight argument'. It puts forward the view that any theory of aesthetic value should characterise aesthetic value in a way that allows for the existence of these arguments. It argues that hedonism does that successfully, but the more recent approaches to aesthetic value--in particular Dominic McIver Lopes's 'Network Theory' have more of a struggle.